PENGARUH SIKAP TERHADAP GURU DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI KEUANGAN - Lia Dwi Septiawati; Raden Gunawan Sudarmanto; Yon Rizal (FKIP Unila, 2013)
This study aimed to determine the effect of teachers' attitudes toward and discipline learning to learning outcomes of financial accounting students at class X Accounting SMK Muhammadiyah 1 Metro Academic Year 2012/2013. The method used in this research is descriptive verification with ex post facto approach and surveys. The results showed that: (1) There is a positive and significant effectt on teacher attitudes towards to learning outcomes of financial accounting students at class X Accounting SMK Muhammadiyah 1 Metro Academic Year 2012/2013. (2) There is a positive and significant effect on discipline learning to learning outcomes of financial financial accounting students at class X Accounting SMK Muhammadiyah 1 Metro Academic Year 2012/2013. (3) There is a positive and significant effect on teachers' attitudes toward and discipline learning to learning outcomes of financial accounting students at class X Accounting SMK Muhammadiyah 1 Metro Academic Year 2012/2013. Keyword : attitudes, discipline and learning outcomes